Digital Media Literacy and Their Role at Elderly Live (Studies Phenomenology at Yang-Eyang School Community at Jember) - Devi Saufa Yardha; Erman Anom; Halomoan Harahap; Iswadi Iswadi (Ilomata International Journal of Social Science, 2023)
This exploratory descriptive phenomenological research aims to understasnd how an elderly person has an understanding of digital media and experiences when using it through theoretical perspectives, concepts, and indicators of digital literacy. Furthermore, this research also explores how to deal with intergenerational communication that occurs between the elderly and children in the context of parenting in the digital media era. Research shows that the elderly have a fairly good, critical, balanced level of understanding about the positive and negative impacts of the internet for their self and their children. Most of the elderly are able to use digital media in their daily lives to communicate, and some others can use digital media to create content. Yang-Eyang also take action to guide the elderly for apply parenting patterns that are adapted to the world of children to build intimacy. Even so, the elderly also implement several strategies to regulate children's use of digital media that run by Yang-Eyang Community.